Effects of logistics planning, human resource management and coordination mediated by individual performance on humanitarian operations performance in Malaysia - Mat Jusoh, Zeti Suzila (2021)
One of the worst catastrophic phenomena hit Malaysia in the year 2014 where the country’s eastern states experienced severe floods, claiming several lives and destructing properties. This study contributes to supporting relevant parties (government agencies and NGOs) in strengthening their future disaster preparedness when dealing with humanitarian aid operations. Undoubtedly, a good operation performance increases organisations’ competitive advantage since inadequate planning, ineffective operations, and lack of coordination between stakeholders are proven to significantly affect operations performance negatively. Existing research on humanitarian operations performance centres mainly on humanitarian organisations, prompting a gap that results in inefficient performance and a lack of professional logisticians in these organisations. The main organisations involved in Malaysian humanitarian operations consist of the government agency, Malaysian Civil Defence Force (MCDF), alongside Non-Governmental Organisations (NGOs) that are registered under NADMA. Generally, the inefficiency in performance and logistical preparation can be reduced by improving the overall performance of the organisations as well as the individual strengths of participating members, thereby strengthening humanitarian aid operations. In Malaysia, the difficulty in improving operations performance proves to be a key challenge for many humanitarian organisations. This issue is compounded by the difficulty to obtain accurate data, limited information technology, chaotic environment, weak motivation, negative media exposure, human resource management issues, general reluctance, and the conflict between long-term and short-term goals. Major concerns have been raised by those who are directly involved in humanitarian projects about the negative performance of these organisations. Thus, this study investigates the impact of logistics preparedness factors (logistics planning, human resource management, and logistics coordination) on humanitarian operations performance with individual performance as a mediator in Malaysia. This study also attempts to fill the gap concerning the contribution and efficiency of individual performance in humanitarian operations performance. This study employs a research framework developed according to the tenets of Resource-Based Theory, Stakeholder Theory, Performance Theory and Goal-Setting Theory. The data was collected from 593 Malaysian respondents who are directly involved in dealing with disasters during humanitarian operations. The data was then analysed using the partial least squares structural equation modelling (PLS-SEM). The findings of the current study reported that the two proposed factors in logistics preparedness, namely (1) human resource management and (2) logistics coordination, are significant predictors of humanitarian operations performance when individual performance functions as a mediator. The mediating role of individual performance is significant in measuring the smoothness and achievement of an operation. In this case, the individual involved is one who carries out operational work and possesses attributes that can facilitate the completion of the task objectives set during the operation. Results also suggest that individual performance concerning logistics preparedness can be achieved by accounting for human resource management and logistics coordination. Moreover, individual performance is also observed to significantly mediate the relationship between human resource management, logistics coordination, and humanitarian operations performance. This study confirms the development of different logistics preparedness factors that can develop and enhance humanitarian operation performance. The managerial implications of the study include (i) the improvement of the individual performance in logistics preparedness to satisfy the needs of the victims, which ultimately contributes to the performance of these humanitarian organisations, and (ii) the resolution of issues related to individual performance via logistics planning, upgrading existing logistics preparedness structures, and introducing preparedness practices. These practices will enhance the performance of humanitarian operations for both individuals and organisations, in line with the policies outlined under the Malaysia National Security Council Directive No. 20. The positive implications will also subsequently benefit the field of disaster management.